Software Development Of Active Power Filter Design For Harmonic Mitigation - Rajab, Ramdan Emhemmed (2002)
The development of design automation tools for a power electronic circuit has received a great deal of attention in the last two decades. To provide an optimum solution for each power electronics application demands the selection of the most appropriate power electronic devices, power circuit and control philosophy. For a certain applications, it must be decided which power circuit topology and which power semiconductor with which control strategy is best suited for it. Their design and fabrication require extensive knowledge and sophistication that must be continually updates as the technologies improve. Considerable engineering effort and knowledge are required to take a power circuit from a laboratory prototype to a finished product. Other than being an expert in areas as diverse as thermal design, circuit and system packaging, circuit protection, and safety and electromagnetic interference regulations.With such a highly demanding expertise required of power electronic circuits' designers and with such rapid advancements in the field of circuit topology and semiconductor devices it is difficult for designers to come up with an optimum circuit and the right device within a short time. If a design aid system that embraces all the elements of power circuitry design of products may be achieved in a short time and quality of the products will be kept on a consistent high level. The developed system is named AFDAS (Active Filter Design Aid System). The system characterized as an intermediate object-oriented system connecting the user with a network of different specialized software packages, without the assumption of the user familiarity with these packages. The implementation includes developing a data base circuits library, generation of formatted files to be used as input streams with the design packages, writing an interface program for each kind of these software's, and managing the data flow timing and dependency among them. In this thesis the circuit topology database development based on PSPICE is presented with examples of single-phase active filter resistive load and three-phase active filter resistive load.